Perception of Supervisor in Practice Teaching - Phuyel, Dil Nath (Namuna Academic Journal, 2025)
The purpose of the present study is to find out the perception of supervisors, namely, campus supervisor, school (internal) supervisor and student-teacher, towards the supervision in practice teaching in a three-year Bachelor of Education (B. Ed.) programme in Tribhuvan University (TU), Nepal. This is based on qualitative and quantitative tools of research. The primary data collected from the field survey, in 2073 B.S., is the base for the estimation of the result of the study. As a whole, the student-teachers and the teacher supervisors (campus supervisor and school supervisor) have a positive attitude towards supervision in the practice teaching programme. However, it has been a common experience as well as a realization among the respondents that they need to be much richer about conducting supervision in the practice teaching programme. The supervisors pay little attention to the student-teacher's behavior in the whole process of practice teaching. All in all, practice teaching has been considered by the stakeholders "as a formality" only.